Patatin, the major protein of potato (Solanum tuberosum L.) tubers, and its occurrence as genotype effect: processing versus table potatoes - Jan BÁRTA; Veronika BÁRTOVÁ (Czech Journal of Food Sciences, 2008)
Patatin relative abundance in SDS-extractable protein and patatin content in dry matter were evaluated in tubers of forty processing and table potato cultivars usually cultivated in the Czech Republic, Germany, and the Netherlands. The patatin characteristics were evaluated over three experimental years. Patatin relative abundance in the processing cultivars achieved on average a significantly higher value (P < 0.001; Tukey HSD test) than patatin relative abundance in the table cultivars, resulting in average values of 25.80% and 21.59%, respectively. A high patatin relative abundance (over 30% in extractable protein) was determined only in the case of two cultivars: Vaneda (average 31.29%) and Tomensa (average 31.24%). Patatin content in tuber dry matter was significantly higher in the processing potato cultivars in all three experimental years (P < 0.001), attaining a mean of 1.28% with the processing cultivars and 1.03% with the table cultivars. The direct effect of the cultivar on patatin relative abundance in SDS-extractable protein was higher (33.1% for processing potato cultivars and 48.1% for table potato cultivars) than the effect of the growing year (15.6% for processing potato cultivar and 22.8% for table potato cultivars).